2019
DOI: 10.1002/pssr.201900270
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Solar Wafer Temperature Measurement during Firing Process via Inline IR Thermography

Abstract: Herein, an inline IR thermography system as an innovative application for real‐time contactless temperature measurement of wafers—both metallized and nonmetallized—during the firing process is successfully realized in an industrial firing furnace as proof of concept and example for a thermography system in a conveyor furnace. As observed by the new system, thermocouples (TCs) seem to measure lower temperature on wafers—especially in combination with TC frames—than wafers exhibit at standard firing conditions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Not to be confused with the previously mentioned contemporaneous temperature distribution, Fig. 3(c) shows the 2-D peak temperature mapping for the laser firing, which is compared to conventional firing (for the latter, discussion of results in [8]. It is clearly visible that the laser-fired wafer experiences a significantly higher spatial temperature inhomogeneity than the conventionally fired wafer.…”
Section: A Wafer Temperature Evaluation During Laser Firingmentioning
confidence: 89%
See 2 more Smart Citations
“…Not to be confused with the previously mentioned contemporaneous temperature distribution, Fig. 3(c) shows the 2-D peak temperature mapping for the laser firing, which is compared to conventional firing (for the latter, discussion of results in [8]. It is clearly visible that the laser-fired wafer experiences a significantly higher spatial temperature inhomogeneity than the conventionally fired wafer.…”
Section: A Wafer Temperature Evaluation During Laser Firingmentioning
confidence: 89%
“…Classic thermocouple measurements [2], as conducted in [3], cannot be realized in the laser peak zone because the installed mirrors leave no space for the thermocouple equipment to pass. Therefore-based on our previous works in [8] and [9] for conventional firing-an inline infrared (IR) camera by InfraTec has been installed outside of the laser chamber [see Fig. 1(a)].…”
Section: A Laser Peak Zone and Its Temperature Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of the VCSEL chamber in transport direction amounts to 80 cm, while the used conventional drying furnace is 230 cm long, making the VCSEL system significantly more compact. The temperature during the VCSEL drying is monitored via IR thermography, [ 21 ] as visualized in Figure 1a. Preliminary tests have revealed that the optimum solar cell temperatures for VCSEL drying are similar to those for conventional drying, namely 170–270 °C—being valid for all three types of the applied metallization steps.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate an alternative firing technology a laser chamber, with laser class 1, right after the heating chamber was set up and a laser system consisting of two VCSEL (vertical cavity emitting surface laser) modules has been integrated (changes in orange) [5]. Furthermore, two positions to realize an optical inspection with an IR camera system have been defined (changes in blue) [6,7]. shows the adapted furnace.…”
Section: Equipment Setup and Perc Solar Cellsmentioning
confidence: 99%